KAJIAN PROSPEK KOMODITAS INDUK UDANG WINDU PADA KAWASAN PESISIR PERAIRAN PANTAI DI DAERAH KABUPATEN ACEH BESAR - M. Yuzan Wardana (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
The Prospect of Tiger Prawn Mother in Aceh Besar Coastal AreaABSTRACT. District of Aceh Besar has a relatively promising prospect of tiger prawn. The district was known for its habitat of best quality species such as Black Tiger, Tiger shrimp or Tiger Prawn. However, the number of this species became rare and therefore import from other regions is needed. The aims of this research are: (1) to identify locations along the districts coasts as the most suitable habitat, (2) to measure the sizes and qualities of tiger prawn which compatible with the commercial standards, (3) to learn the best distribution and marketing methods which is able to keep benur dan induk udang alive.. This research was done in 3 Subdistrics (Peukan Bada, Lhoknga and Baitussalam) using purposive sampling method. The results showed that the location were suitable for hatcheries, the quality and size already match with the requirements shown by the weight, egg contains level is high, the body shapes are normal and clean from parasite, using local tiger prawn mother may minimize the cost. The effort such as injecting oxygen and assuring the quality of packages indicated as best distribution method.